(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Image Processing is very popular topic in the field of research and development. Image processing is a large research area to improve the visibility of an input image and acquire some valuable information from it. In Image processing any form of signal processing for which the input is an digital image; the output of image processing can be either an image or a set of characteristics or parameters related to the image. Most imageprocessing techniques involve treating the image as a two-dimensional signal and applying standard signal-processing techniques to it. This paper presents basics of digital image processing. Image processing were developed in 1960s and in 2000 digital image processing has become the most common form of image processing due to its versatility and low cost. In broader sense, Image processing is divided into two major branches; image enhancement and image restoration. Fourier transform is most popular image transforms. The Fourier Transform is used in a wide range of applications. Image Processing is the act of examining images for the purpose of identifying objects and judging their significance. An image analyst studies the remotely sensed data and attempt to detect, identify, classify, measure and evaluate the significance of physical and cultural objects, their patterns and spatial relationship through logical processes